Крылья крепнут в бою: [Докум. повесть] / Василий Голубев - Голубев Василий Федорович (Сов. Россия, 1980)
Экземпляры: (20181025) / Инвентарный номер: 7091 / Цена: 0.70 / Сис.шифр: 9(С)27 / Авт.знак: Г62 / ББК: 9(С)27